(untitled) (Global Journals of Research in Engineering, 2012)
Based on the concept of the external power system dynamic equivalent for the study system, this paper proposes a novel evolutionary method for the identification of the equivalent#x2019;s parameters, comparing the answers of the complete network and its equivalent following the small disturbances which emerged in the study system. The proposed method is demonstrated and compared with the original system using the 10 machines 39 buses New England test system. The comparison shows that the proposed approach can preserve all dynamic properties of the original network.